Oxidative stress in ARDS: mechanisms and therapeutic potential - Wang, Fengyun; Ge, Ruiqi; Cai, Yun; Zhao, Mingrui; Fang, Zhen; Li, Jingguo; Xie, Chengzhi; Wang, Mei; Li, Wanyue; Wang, Xiaozhi (Frontiers in Pharmacology, 2025)
Acute respiratory distress syndrome (ARDS) is a life-threatening condition characterized by acute lung inflammation, increased vascular permeability, and hypoxemic respiratory failure. Oxidative stress, driven by excessive reactive oxygen species (ROS), is a key contributor to ARDS pathogenesis, causing cellular damage, inflammation, and alveolar-capillary barrier disruption. This review elucidates the mechanisms of oxidative stress in ARDS, focusing on ROS production via NADPH oxidase (NOX) and mitochondria, which activate pathways like NF-κB and MAPK, promoting pro-inflammatory cytokine release. ROS-induced lipid and protein peroxidation, endothelial dysfunction, and programmed cell death (PCD), including apoptosis, pyroptosis, and ferroptosis, exacerbate lung injury. In COVID-19-related ARDS, SARS-CoV-2 spike protein amplifies mitochondrial ROS, worsening outcomes. Antioxidant therapies falter due to non-specific ROS suppression, patient heterogeneity (e.g., GSTP1 polymorphisms), and poor bioavailability. We propose a model where oxidative stress drives ARDS stages—early alveolar injury and late systemic dysfunction—suggesting targeted therapies like endothelial-specific nanoparticles or ferroptosis inhibitors. Precision medicine using biomarkers (e.g., mtDNA) and gender-specific approaches (e.g., estrogen-Nrf2 regulation) could enhance outcomes. This review bridges mechanistic gaps, critiques therapeutic failures, and advocates novel strategies like mitochondrial-targeted therapies to improve ARDS management.